1999
DOI: 10.1152/jappl.1999.87.5.1990
|View full text |Cite
|
Sign up to set email alerts
|

Chronic activation of 5′-AMP-activated protein kinase increases GLUT-4, hexokinase, and glycogen in muscle

Abstract: This study was designed to determine whether chronic chemical activation of AMP-activated protein kinase (AMPK) would increase glucose transporter GLUT-4 and hexokinase in muscles similarly to periodic elevation of AMPK that accompanies endurance exercise training. The adenosine analog, 5-aminoimidazole-4-carboxamide ribonucleoside (AICAR), has previously been shown to be taken up by cells and phosphorylated to form a compound (5-aminoimidazole-4-carboxamide ribonucleotide) that mimics the effect of AMP on AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
347
9
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(387 citation statements)
references
References 35 publications
27
347
9
4
Order By: Relevance
“…During chronic AMPK activation, AMPKstimulated glucose uptake may override inhibition of glycogen synthase by AMPK, resulting in enhanced glycogen storage. Similar effects of glycogen supercompensation have been previously observed in AICARtreated Sprague-Dawley rats [32]. However, further AMPK activation through acute AICAR stimulation resulted in a decrease in glycogen levels in myotubes from control and R225W carriers.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…During chronic AMPK activation, AMPKstimulated glucose uptake may override inhibition of glycogen synthase by AMPK, resulting in enhanced glycogen storage. Similar effects of glycogen supercompensation have been previously observed in AICARtreated Sprague-Dawley rats [32]. However, further AMPK activation through acute AICAR stimulation resulted in a decrease in glycogen levels in myotubes from control and R225W carriers.…”
Section: Discussionsupporting
confidence: 83%
“…The increase in plasma fatty acids in R225W carriers during exercise may indicate a blunted increase in fatty acid uptake in muscle in response to exercise, stemming in turn from a greater proportional reliance on endogenous glucose and glycogen fuel stores in the muscle of individuals with the PRKAG3 R225W mutation. The mechanism responsible for a greater glucose uptake in R225W carriers during exercise may be elevated skeletal muscle GLUT4 levels, which has been previously demonstrated in Sprague-Dawley rats chronically treated with AICAR [32]. However, GLUT4 (also known as SLC2A4) expression in the control and R225W primary human myotubes was undetectable via quantitative RT-PCR (data not shown).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Several studies have shown that 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR), an AMPK activator, activates glucose transport and increases the expression of glucose transporter 4 (GLUT4) and several metabolic enzymes in skeletal muscle (Buhl et al, 2001;Holmes et al, 1999Holmes et al, , 2005Ojuka et al, 2002;Stoppani et al, 2002;Winder et al, 2000;Zheng et al, 2001). It has been reported that an increase in glucose uptake induced by AICAR results in increased lactic acid production in isolated rat skeletal muscle (Miyamoto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…AMPK is activated during exercise and has been termed a master metabolic switch because it phosphorylates key target proteins that control the flux through metabolic pathways. Chronic activation of AMPK by injection of the adenosine analog 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) into rats results in an increase in GLUT-4 protein in vivo 21) ; the same pattern occurs when isolated rat muscles are exposed to AICAR in vitro 22) . Furthermore, AMPK phosphorylates GEF 23) and the transcription repressor histone deacetylase 5 (HDAC5) 24) .…”
Section: Mechanisms Underlying Exercise-induced Glut-4 Biogenesismentioning
confidence: 99%